Numerical simulation of bond-slip interface and tension stiffening in GFRP RC tensile elements. (1st October 2016) - Vilanova, I.; Torres, L.; Baena, M.; Llorens, M.
Abstract: Bond between reinforcement and concrete highly affects the structural behaviour of reinforced concrete (RC). Introduction of bond-slip models into numerical simulation allows taking into account the bond interaction and analyse its effect on local and global behaviour. Unlike conventional steel reinforcement, no standard bond-slip law exists for FRP reinforcement, as bond is the result of a combination of parameters such as reinforcing material and bar surface configuration, among others. Therefore, there is a need in developing a methodology to easily implement bond-slip response from experimental bond tests. In this work, a methodology to implement bond-slip behaviour between concrete and reinforcement into a FEM model is presented. The inverse analysis is used to characterise the bond mechanisms active in a pull-out test. The obtained constitutive behaviours are thereafter implemented into a FE program by using connector elements and surface-to-surface contacts, and GFRP RC tensile elements are modelled. Numerical results are compared to experimental ones available in the literature, showing good accuracy in terms of load-deformation, crack width and crack spacing, as well as strains and bond stress and slip distributions along the reinforcing bar.